Assessing the Dynamics of the Moulay Bousselham Lagoon: An Integrated DPSIR Approach to Understand Drivers, Impacts, and Human Response - Nouhaila Erraj Chahid; Mohammed Bouchkara; Donata Melaku Canu; Khalid El Khalidi; Bendahhou Zourarah (Proceedings)
Currently, the Moulay Bousselham lagoon faces a pressing issue of sediment buildup, particularly in the inlet zone, which has led to the formation of sandy areas known as “sandpits” and poses the threat of inlet closure. This environmental challenge has significant implications for the lagoon’s ecological well-being and the local economy. In response to this issue, decision-makers have initiated a comprehensive study to identify viable hydrodynamic solutions that can effectively mitigate sediment deposition and improve the lagoon’s overall conditions. The primary objective of this study is to investigate the complex interplay between socio-economic factors and their impacts on the lagoon environment. To accomplish this, a DPSIR (Driving forces-Pressures-States-Impacts-Responses) framework is adopted. This framework facilitates the analysis of causal relationships among various elements, such as economic sectors, human activities (driving forces), resulting emissions and waste (pressures), the physical, chemical, and biological condition of the lagoon (states), and the ecological, societal, and economic consequences (impacts). By understanding these connections, appropriate policy responses can be formulated, including prioritization, target setting, and the development of relevant indicators. In addition to the comprehensive assessment of the lagoon’s socio-economic and environmental dynamics, this study also proposes management strategies that balance the current state of the lagoon with the long-term ecological sustainability and the well-being of the local population. By considering the unique challenges faced by the Moulay Bousselham lagoon and exploring feasible solutions, this research aims to guide decision-making processes and contribute to the preservation and effective management of this valuable coastal ecosystem.